Unveiling the fructose metabolism system in Staphylococcus aureus: insights into the regulatory role of FruR and the FruRKT operon in bacterial fitness - Yan Ge; Daiyu Li; Ning Wang; Yun Shi; Gang Guo; Liyuan Fang; Quanming Zou; Qiang Liu (BMC Microbiology, 2024)
Abstract Background The utilization of fructose as a carbon source and energy provider plays a crucial role in bacterial metabolism. Additionally, fructose metabolism directly impacts the pathogenicity and virulence of certain pathogenic microorganisms. Results In this study, we report the discovery of a fructose phosphotransferase system (PTS) in S. aureus. This system comprises three genes, namely fruR, fruK, and fruT, which are co-located in an operon that is indispensable for fructose utilization in S. aureus. Our findings confirm that these three genes are transcribed from a single promoter located upstream of the fruRKT operon. The fruR gene encodes a DeoR-type transcriptional regulator, designated as FruR, which represses the expression of the fruRKT operon by direct binding to its promoter region. Significantly, our experimental data demonstrate that the fruRKT operon can be induced by fructose, suggesting a potential regulatory mechanism involving intracellular fructose-1-phosphate as a direct inducer. Furthermore, we conducted RNA-seq analysis to investigate the specificity of FruR regulation in S. aureus, revealing that the fruRKT operon is predominantly regulated by FruR. Conclusions In summary, this study has uncovered a fructose phosphotransferase system (PTS) in S. aureus, highlighting the essential role of the fruR, fruK, and fruT genes in fructose utilization. We confirmed their co-location within an operon and established FruR as a key regulator by binding to the operon’s promoter. Importantly, we demonstrated that fructose can induce this operon, possibly through intracellular fructose-1-phosphate. Our identification of this PTS system represents the initial characterization of a fructose metabolism system in S. aureus.